The Old World and New World Connections to the Porcelain-Inlaid Earthenware Found in the Philippines - Arriola, Donna (Hukay; Vol 9 (2006), 2016)
Two sherds of earthenware that were decoratively inlaid with chips of broken porcelain called "porcelain-inlaid earthenware" were unearthed in the 2005 Archaeological Impact Assessment of ACECI in San Agustin Museum, Intramuros. This led to this preliminary research on the origins and distribution of this type of pottery, revealing similar types present in Iberia, the Americas and Africa. The article presents a connection between our local type of inlaid earthenware with those found in the aforementioned regions as suggested by archaeological, ethnological, and historical data while establishing that the porcelain-inlaid earthenware found in the Philippines is, although related, a distinct local type.